2002
DOI: 10.1084/jem.20020170
|View full text |Cite
|
Sign up to set email alerts
|

Essential and Instructive Roles of GATA Factors in Eosinophil Development

Abstract: GATA transcription factors are major regulators of hematopoietic and immune system. Among GATA factors, GATA-1, GATA-2, and GATA-3 play crucial roles in the development of erythroid cells, hematopoietic stem, and progenitor cells, and T helper type 2 (Th2) cells, respectively. A high level of GATA-1 and GATA-2 expression has been observed in eosinophils, but their roles in eosinophil development remain uncertain both in vitro and in vivo. Here we show that enforced expression of GATA-1 in human primary myeloid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
161
0
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(169 citation statements)
references
References 29 publications
5
161
0
3
Order By: Relevance
“…75 Recent studies have shown that even the simple ectopic expression of both PU.1 and C/EBPa within mesenchymal stem cell-derived fibroblasts is sufficient to activate the myeloid program resulting in an induced macrophage-like phenotype capable of phagocytosis. 76 Finally, enforced expression of GATA-1 leads to reprogramming of myeloblasts and CD34 þ bone marrow cells into eosinophils, 77,78 whereas within mouse granulocyte-monocyte progenitors ectopic GATA-1 can reprogram these cells to adopt erythroid, eosinophilic or basophile-like properties. 79 The above-described observations show that PU.1 and GATA-1 act as 'the motors for reprogramming' and this correlation could be very useful with regard to the application of 'differentiation therapy' whereby re-establishing the correct expression of PU.1 and or GATA-1 within immature leukemic cells, or those attempting to mature into an unwanted lineage should reprogram and differentiate these cells back into their respective cellular lineage.…”
Section: Pu1 and Gata-1 Interact During Early Hematopoietic Cell Decmentioning
confidence: 99%
“…75 Recent studies have shown that even the simple ectopic expression of both PU.1 and C/EBPa within mesenchymal stem cell-derived fibroblasts is sufficient to activate the myeloid program resulting in an induced macrophage-like phenotype capable of phagocytosis. 76 Finally, enforced expression of GATA-1 leads to reprogramming of myeloblasts and CD34 þ bone marrow cells into eosinophils, 77,78 whereas within mouse granulocyte-monocyte progenitors ectopic GATA-1 can reprogram these cells to adopt erythroid, eosinophilic or basophile-like properties. 79 The above-described observations show that PU.1 and GATA-1 act as 'the motors for reprogramming' and this correlation could be very useful with regard to the application of 'differentiation therapy' whereby re-establishing the correct expression of PU.1 and or GATA-1 within immature leukemic cells, or those attempting to mature into an unwanted lineage should reprogram and differentiate these cells back into their respective cellular lineage.…”
Section: Pu1 and Gata-1 Interact During Early Hematopoietic Cell Decmentioning
confidence: 99%
“…GATA-2 promotes the proliferation and survival of multipotent precursors (2, 3), whereas GATA-1 regulates erythroid, megakaryocyte, and eosinophil differentiation (4)(5)(6)(7). GATA factors engage DNA and coregulators via a dual zinc finger domain (8), and other regions modulate activity (9,10).…”
mentioning
confidence: 99%
“…Aunque hay células de la inmunidad innata que producen IL-4 e IL-13, los linfocitos son necesarios para la producción de IgE, pues a través de señales por contacto intercelular (CD40/CD40L) inducen el cambio de isotipo en los linfocitos B hacia la cadena pesada épsilon (16). Los teleósteos, que datan de hace más de 300 millones de años, tienen varios genes que codifican para componentes de la respuesta Th2 (17), así como células efectoras (mastocitos, eosinófilos y basófilos) que se activan frente a ciertos estímulos antigénicos de una manera similar a como lo hacen las de los mamíferos (18), lo cual sugiere que desde la aparición de los peces se dio una respuesta inmunitaria parecida a la que conocemos ahora como alérgica.…”
Section: Algunos Aspectos De La Filogenia De La Respuesta Th2unclassified
“…Los de origen filogenético más ancestral y mejor caracterizados provienen del pez cebra, Danio rerio, especie que se ha convertido en un buen modelo general para estudiar la respuesta inmunológica de los vertebrados. Balla, et al, aislaron eosinófilos de este pez mediante GATA-2, un marcador celular descrito originalmente en los eosinófilos del ratón (18), y observaron que tenían similitud tanto morfológica como de expresión génica con los eosinófilos de mamíferos. Aunque se detectaron transcriptos de genes que se expresan en los gránulos (ARNasas, principalmente), no se hallaron homólogos de otras proteínas de importancia funcional como la proteína básica mayor y la peroxidasa de eosinófilos.…”
Section: Células De La Inmunidad Innataunclassified